2018
DOI: 10.3389/fpsyg.2018.02415
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Syntax and Proto-Syntax: Evolutionary Dimension

Abstract: The present fMRI study tested predictions of the evolution-of-syntax framework which analyzes certain structures as remnants (“fossils”) of a non-hierarchical (non-recursive) proto-syntactic stage in the evolution of language (Progovac, 2015, 2016). We hypothesized that processing of these structures, in comparison to more modern hierarchical structures, will show less activation in the brain regions that are part of the syntactic network, including Broca’s area (BA 44 and 45) and the basal ganglia, i.e., the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 78 publications
0
16
1
Order By: Relevance
“…While we did not find a contrasting effect in Broca's area, we found that transitives, contrasted with middles, evoked greater activation in the precentral gyrus (BA 6), proposed to be part of the "Broca's complex" (Ardila et al 2016). In a related fMRI experiment (Progovac et al 2018b), we tested the processing of English full sentences with TPs (e.g. The case is closed; The apology is accepted), contrasted with TP-less small clauses (Case closed; Apology accepted), and found a significant difference in both Broca's left BA 44 and right basal ganglia for full (TP) sentences vs. (TPless) small clauses, affirming the relevance of Broca's-basal ganglia network for the processing of more articulated, layered syntax.…”
Section: Fossil Middles Split-accusativity and The Processing Of Thcontrasting
confidence: 79%
See 1 more Smart Citation
“…While we did not find a contrasting effect in Broca's area, we found that transitives, contrasted with middles, evoked greater activation in the precentral gyrus (BA 6), proposed to be part of the "Broca's complex" (Ardila et al 2016). In a related fMRI experiment (Progovac et al 2018b), we tested the processing of English full sentences with TPs (e.g. The case is closed; The apology is accepted), contrasted with TP-less small clauses (Case closed; Apology accepted), and found a significant difference in both Broca's left BA 44 and right basal ganglia for full (TP) sentences vs. (TPless) small clauses, affirming the relevance of Broca's-basal ganglia network for the processing of more articulated, layered syntax.…”
Section: Fossil Middles Split-accusativity and The Processing Of Thcontrasting
confidence: 79%
“…kill-joy; pick-pocket; cry-baby) vs. hierarchical compounds (e.g. joy-kill-er; boot-licker; whistle-blow-er) and found a robust effect in the fusiform gyrus area (BA 37) (Progovac et al 2018b), the area where visual processing and certain non-compositional semantic processing (e.g. concreteness, metaphor) come together (e.g.…”
Section: Fossil Compounds Verbal Aggression and Sexual Selectionmentioning
confidence: 99%
“…In truth, vivid compounds and ideophones may share other features of interest, including possibly a common neurobiological substrate. As shown by Progovac and colleagues [50]), two-slot compounds (the kill-joy type), in contrast with the more complex - er counterparts (i.e. joy-kill-er type), recruit the fusiform gyrus area (specifically BA37), the visual area that is also implicated in synaesthesia, a condition entailing abnormally enhanced cross-modal activity (more on this in the next section).…”
Section: Cross-modality and Aggression: Two Dimensions Of Linguistic ‘Fossils’mentioning
confidence: 93%
“…A second interesting feature of these compounds is their raw, visceral effect (e.g. [45,50]), and particularly, their great propensity for verbal aggression. In many cultures, comparable compositions are used in verbal duels/contests, whose purpose seems to be to replace physical fighting, thus contributing to a better survival of those who engage in verbal, as opposed to physical, duels (for more discussion, see e.g.…”
Section: Cross-modality and Aggression: Two Dimensions Of Linguistic ‘Fossils’mentioning
confidence: 99%
“…While in some cases one may be justified in positing a null category, this blanket declaration of uniformity takes away the tools necessary for deciding when this is justified, and when not, giving rise to a host of unfalsifiable claims. Such sweeping claims are also harmful for biological considerations, because it is exactly the variability, the contrasts and comparisons among different constructions, that reveal the evolutionary primitives of syntax (e.g., Progovac, 2015, 2016), which can also be used to probe language variation and language representation in the brain (e.g., Progovac et al, 2018a,b).…”
Section: Syntactic Uniformity Across Languages and Constructionsmentioning
confidence: 99%